Partisipasi Dosen dan Mahasiswa Prodi Kebidanan STIKes Akbidyo dalam Pelaksanaan Sub Pekan Imunisasi Nasional Polio Putaran 1 Di wilayah kerja Puskesmas Sewon II - Endang Khoirunnisa, Endang; Isabella Rahmawati (ABDIMAS Madani, 2025)
Polio is a public health problem that has long been fought, but a wave of polio resurgence has raised new concerns. The academic community and Sub PIN Polio activities play an important role in efforts to prevent and control the disease, rapid response to detected cases, and cross-sector collaboration are key factors that can be used as examples in handling public health emergencies. This Community Service aims to evaluate the contribution of lecturers and students of the D III midwifery study program, Akbidyo College of Health Sciences and Sewon II Community Health Center in dealing with the first wave of polio cases, as well as anticipating the occurrence of further polio cases, as well as recommendations for improving the response to this health emergency. . The community service method is to send the academic community, namely lecturers and students, to help make the Polio sub-PIN round 1 a success in the Sewon II Community Health Center working area, Sewon City. The results of this Community Service show that the contribution of the D III Midwifery Study Program STIKes Akbidyo and Sub PIN Polio in handling the first wave of polio cases has been significant. Improved immunization programs, public education, case monitoring, and collaboration with various parties have been key factors in suppressing the spread of polio. From the Community Service activities it can be concluded that the contribution of the academic community of STIKes Akbidyo and Sub PIN Polio in handling the first wave of polio cases has played an important role in suppressing the spread of this disease. Apart from that, by participating in community service activities